2019
DOI: 10.26786/1920-7603(2019)532
|View full text |Cite
|
Sign up to set email alerts
|

Plant-pollinator interactions in East Asia: a review

Abstract: Pollination studies in East Asia have been developing rapidly in recent decades. East Asia may provide important information on many aspects of plant-pollinator interactions because of the rich fauna and flora and highly heterogeneous environments that occur there. In this review, plant-pollinator interactions in East Asia were summarized. Bumblebees are important pollinators of many plant species in East Asia, as well as in Europe and North America. Native honeybees may also have important roles in pollinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 272 publications
(444 reference statements)
1
12
0
Order By: Relevance
“…Information on plant–mammal interactions in montane forests, especially pollination‐mediated relationships, is still lacking in tropical Asia (Corlett, 2004 ; Funamoto, 2019 ), although it has been reported that non‐flying mammals contribute to pollination in other montane regions (Dellinger et al, 2019 ; Lumer, 1980 ). The present study showed that non‐flying mammals may play an important role as pollinators in tropical montane forests, although the sample size was insufficient.…”
Section: Resultsmentioning
confidence: 99%
“…Information on plant–mammal interactions in montane forests, especially pollination‐mediated relationships, is still lacking in tropical Asia (Corlett, 2004 ; Funamoto, 2019 ), although it has been reported that non‐flying mammals contribute to pollination in other montane regions (Dellinger et al, 2019 ; Lumer, 1980 ). The present study showed that non‐flying mammals may play an important role as pollinators in tropical montane forests, although the sample size was insufficient.…”
Section: Resultsmentioning
confidence: 99%
“…In another Japanese mountain region (the Taisetsu mountains), flowers are dominantly visited by bees and flies at the community level (Mizunaga & Kudo, 2017 ). A recent review has reported that Lepidoptera account for less than 10% of insect visitors to flowers in many parts of Asia, whereas bees and flies account for more than half (Funamoto, 2019 ). It is possible that in the central Japanese Alps, because only the locally abundant bumblebees contribute to pollination of A. buergeriana var.…”
Section: Discussionmentioning
confidence: 99%
“…However, consequences of plant-pollinator interactions are geographically variable (Hiraiwa and Ushimaru 2017;Johnson et al 2017;Ollerton 2012;Ollerton 2017;Zanata et al 2017), and this variation is still not well documented and difficult to elucidate owing to various factors associated with pollination (Ollerton 2012). While many gymnosperm plants depend on the wind and water for their pollination (Funamoto 2019;Khalifa et al 2021), animal pollinators including insects, bats and birds have contributed to pollination and seed production of angiosperms. Most of flowering plants are not dependent on just one pollinator, but involve a broad spectrum of pollinators.…”
Section: Introductionmentioning
confidence: 99%